To Help or Not to Help: A First Year Canadian Medical Student's Dilemma During the COVID-19 Pandemic - Janhavi Patel (University Library System, University of Pittsburgh, 2020)
I am a first-year medical student, and this is a commentary, highlighting some of the dilemmas and challenges encountered by a first-year medical student during these unprecedented times of the COVID-19 crisis. With the declaration of COVID-19 as a public health emergency, and medical students having to discontinue their clinical duties, I felt apprehensive. As if being restricted from serving the communities for whom I took an oath of service, even before I could start. Talking with my mentors and through self-reflection, I found solace in diverting my energy in supporting the frontline staff from the bleachers. This article would provide medical students with an opportunity to think critically during these times, stir conversation amongst medical students, and allow them to recognize how to reconcile with so much uncertainty about the future.